Технологія видалення рідини з експлуатаційної колони глибокої свердловини - Римчук, Данило Васильович (НТУ "ХПІ", 2015)
Проведений аналіз факторів, які впливають на якість освоєння та дослідження свердловин. Запропоновано спосіб видалення рідини з експлуатаційної неперфорованої та перфорованої колон глибокої свердловини. Приведена схема облаштування гирла та вибою свердловини при видаленні рідини з експлуатаційної неперфорованої колони та технологія видалення рідини з експлуатаційної перфорованої колони. Описаний порядок вилучення внутрішньої колони ліфтових труб із свердловини після видалення рідини і отримання припливу флюїду при перфорованій експлуатаційній колоні.

The analysis of factors affecting the quality of research and development wells. These existing methods of removing fluid from the well and call methods inflow of fluid. A new way to remove fluid from the operational punched and perforated columns deep wells. Present location and arrangement of the mouth of the bottom hole while removing fluid from the operational technology punched columns and removing fluid from the operational perforated column. The described procedure for extracting internal column lift pipes from the well after the removal of fluids and get influx of fluid in the perforated production string. Designated way communication pipe space outdoor column lift pipes from the production string after removing the inner column lift pipes for the introduction of wells in operation. Analyzed the design of devices for the installation of the bottom of the elevator pipes.
Technology removal of fluid from the deep hole production string
Keywords: ліфтові труби; внутрішньотрубний простір; кільцевий простір; зворотний клапан; in-line space; annular space; check valve; lift pipes